Improving Mathematics Learning Outcomes Through Interactive Electronic Modules Based on Constructivism and Cone of Experience - Bela Desy Natalia; Candra Ditasona; Stevi Natalia (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2025)
Indonesia is projected to achieve its golden era by 2045, necessitating significant adaptation and transformation in cultivating high-quality human resources through education. However, the persistent issue of low mathematics achievement and the predominance of Teacher-Centered Learning (TCL) approaches at SMAN 14 Jakarta highlights the need for educational innovation. This study aims to design and develop an interactive electronic module grounded in constructivist pedagogy by incorporating Edgar Dale's Cone of Experience to enhance students' proficiency in the topic of counting principles. Key challenges include limited conceptual comprehension among students, inadequately aligned learning resources, and assessment strategies that fail to reflect instructional objectives. Employing a Research and Development (RnD) methodology, this study adopts the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) for systematic module development. The findings demonstrate that the module exhibits excellent validity, with mean scores for content, media, and language validation of 3.6, 3.9, and 3.8, respectively. The module further demonstrates substantial effectiveness, achieving a 70% improvement rate based on the n-gain test, which highlights a statistically significant enhancement in students' learning outcomes. Additionally, the practicality assessment yields high practicality, with an r-value exceeding the r-table and a practicality percentage of 92%. This study concludes that the developed module is highly effective in improving mathematical achievement, exhibits practical utility in instructional settings, and possesses robust validity for educational implementation.